2003
DOI: 10.1002/biof.5520190111
|View full text |Cite
|
Sign up to set email alerts
|

Isolated erythrocyte membranes of transfusion‐dependent and non‐transfused thalassemia patients in Jakarta, investigated by electron paramagnetic resonance spectroscopy

Abstract: Erythrocyte membrane structural parameters were studied in transfusion-dependent beta-thalassemia patients, in long-term transfused patients (regularly transfused < 15 years), and in those who had not yet obtained transfusions. Controls were voluntary students up to 30 years of age without diagnosis or clinical signs of thalassemia. Membranes were isolated and investigated by sodium dodecylsulfate polyacrylamide gel electrophoresis (SDS-PAGE) and electron paramagnetic resonance (EPR) spectroscopy. Data obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Vice versa, parameters of lipid peroxidation increase, measured as TBARs, e.g., MDA, a parameter of membrane damage. This is confirmed by the investigation of isolated red cell membranes by ESR spectroscopy and SDS-PAGE [27].…”
Section: Discussionsupporting
confidence: 57%
“…Vice versa, parameters of lipid peroxidation increase, measured as TBARs, e.g., MDA, a parameter of membrane damage. This is confirmed by the investigation of isolated red cell membranes by ESR spectroscopy and SDS-PAGE [27].…”
Section: Discussionsupporting
confidence: 57%
“…5 In the frame of our previous studies, we reported on hematology, iron overload, imbalanced antioxidant status 6 and changes in characteristics of isolated RBC membranes in thalassemic patients in Jakarta. 7 Now, we compare the plasma lipid pattern under oxidative stress with parameters of isolated RBC membranes from thalassemic patients measured with electron paramagnetic resonance spectroscopy using doxyl-stearic acid spin labels and thiol-reactive N-proxyl-maleimide spin label.…”
mentioning
confidence: 99%
“…Free iron can generate reactive oxygen species (ROS), which cause damage to tissues, especially to the liver and the heart (8)(9)(10). Excess iron in the body must be treated with iron chelators (11,12), e.g., deferoxamin (DFO) as one of the standard drugs.…”
Section: Estuningtyas Et Almentioning
confidence: 99%